N-Formyl-L-aspartate mediates chemotaxis in sperm via the beta-2-adrenergic receptor - Panchal, Durva; Bhagwat, Shweta; Parte, Priyanka (Frontiers in Cell and Developmental Biology, 2022)
Chemotaxis is a highly conserved physiological event required for directed sperm movement during fertilization. Recently, studies from our laboratory have identified N-Formyl-L-aspartate (NFA) as a sperm chemoattractant. NFA is a known agonist for the beta-2-adrenergic receptor (β-2-AR) that regulates cAMP production and Ca2+ mobilization in somatic cells. As these downstream signaling molecules are also reported to be involved in sperm chemotaxis, in the present study we investigated the putative mechanism/s by which NFA may mediate chemotaxis. Towards this, the expression and localization of β-2-AR in sperm was studied by western blot and indirect immunofluorescence, respectively. The responses of sperm to -various concentration gradients of NFA and ICI-118,551, a β-2-AR specific antagonist were evaluated using the microfluidics device-based chemotaxis assay. The intracellular concentration of Ca2+, on exposure to NFA was analyzed using FURA-2 AM-based fluorimetric assay. Further, the effect of NFA on sperm capacitation and acrosome reaction was evaluated using western blot and immunofluorescence. NFA exhibited a bell-shaped dose-response curve typical of chemotaxis, with maximum response observed at 0.01M NFA, beyond which it was inhibitory; β-2-AR localization was seen on sperm head and mid-piece region of the flagella. Inhibition of sperm chemotaxis by ICI-118,551 confirms that sperm respond chemotactically to NFA via β-2-AR. Interestingly, at the concentration used for chemotaxis, NFA induced an increase in the intracellular Ca2+ but decreased cAMP in capacitating sperm. However, NFA per se did not induce capacitation as seen from the lack of effect on tyrosine phosphorylation, and membrane potential of uncapacitated sperm. Acrosome evaluation of NFA treated sperm using PSA-FITC staining showed no effect on acrosome structure. Our data thus provides evidence indicating that NFA induces sperm chemotaxis and the chemotactic response of sperm to NFA from ovulatory phase oviductal fluid is mediated through the β-2-AR on sperm possibly via the non-canonical signaling.